Nitrogen-doped carbon nanosheets with size-defined mesopores as highly efficient metal-free catalyst for the oxygen reduction reaction - Wei, Wei; Liang, Haiwei; Parvez, Khaled; Zhuang, Xiaodong; Feng, Xinliang; Muellen, Klaus (Angewandte Chemie International Edition, 2014)
Nitrogen-doped carbon nanosheets (NDCN) with size-defined mesopores are reported as highly efficient metal-free catalyst for the oxygen reduction reaction (ORR). A uniform and tunable mesoporous structure of NDCN is prepared using a templating approach. Such controlled mesoporous structure in the NDCN exerts an essential influence on the electrocatalytic performance in both alkaline and acidic media for the ORR. The NDCN catalyst with a pore diameter of 22 nm exhibits a more positive ORR onset potential than that of Pt/C (-0.01 V vs. -0.02 V) and a high diffusion-limited current approaching that of Pt/C (5.45 vs. 5.78 mA cm-2) in alkaline medium. Moreover, the catalyst shows pronounced electrocatalytic activity and long-term stability towards the ORR under acidic conditions. The unique planar mesoporous shells of the NDCN provide exposed highly electroactive and stable catalytic sites, which boost the electrocatalytic activity of metal-free NDCN catalyst. Nitrogen doping: Mesoporous nitrogen-doped carbon nanosheets with defined mesopore size of 22 nm exhibits outstanding oxygen reduction reaction performance comparable to that of the Pt/C catalyst in alkaline medium (see picture), pronounced activity, and long-term stability under acidic conditions. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene; mesoporous materials; metal-free catalysts; nitrogen doping; oxygen reduction reaction